Pengaruh Sumberdaya Manusia, Orientasi Pasar, Orientasi Kewirausahaan terhadap Strategi Bersaing dan Kinerja Rumah Sakit (Studi Pada Rumah Sakit Umum Daerah di Jawa Timur) - Muchtolifah (Universitas Brawijaya, Indonesia, 2009)
Market and entrepreneurship orientation is an organization capability that provides some contribution to the unique creation of resources and positional advantage. The optimum effect to performance is achieved when there is an adjustment between market orientation and entrepreneurship. Human resources with their level of capabilities, experience and high skills are able to overcome the uncertainty in the working environment. The objective of this study is to measure the effect of human resources development, market and entrepreneurship orientation to the competitive strategy and company performance at Regional Public Hospitals in East Java. The study was conducted at the 16 Regional Public Hospitals of type B and C in East Java Province with 179 respondents, consisting of the directors, the vice directors, the chiefs of division and sub-division. The sampling technique was multi stage sampling consisted of two stages, namely: determining the sample frame and unit analysis. While the variables were human resources development, market orientation, entrepreneurship orientation, competitive strategy and company performance. The data were analyzed by using Structural Equation Modeling (SEM)/ . The result of study implies that the low level of human resources development and entrepreneurship orientation make the role of human resources development and entrepreneurship orientation to the competitive strategy and also the role as a mediator of the effect of market orientation to the performance of regional public hospital less effective. Market orientation as an organization capability has become the concept and philosophy in the regional hospital management. The competitive strategy that focused on the market orientation can increase the performance of regional public hospital. This means that the implementation of competitive strategy would be effective if it is supported by the organization resources, such as market orientation that has become the hospital's policy and competence.